WHY HEALTH WORKFORCE MATTERS: REFLECTIONS FROM CURRENT PANDEMIC AND PAST PROGRAMS EXPERIENCES - Nur Atika (Universitas Airlangga, 2020)
A well-functioning health system depends largely on the quantity and capacity of health human resources who have responsibilities for organizing and implementing health services. A proper arrangement of health workers in terms of numbers, competencies, and diversity is necessary for responding to healthcare needs and achieving health program goals. The need for adequate and skilled health professionals has become even more urgent in the time of current pandemic situation to ensure the resiliency of health systems. In responding to the COVID-19 pandemic, especially in Indonesia, attention is intensively paid to the aspect of facilities such as hospitals, as well as testing and protective equipment. However, we should not forget that the readiness of human resources including clinicians, nurses, laboratory staff, ambulance drivers, and so on are also of paramount importance.